Success and Failure of European Settler Farming in Colonial Africa - Ewout Frankema; Erik Green; Ellen Hillbom (African Economic History Network (AEHN), 2014)
This paper ties into a new literature that aims to quantify the long-term economic effects of historical European settlement, arguing for the need to properly address the role of indigenous agency in path-dependent settlement processes. We conduct three comparative case studies in West, East and Southern Africa, showing that the successes of European settler farming were often of a temporary nature and that they critically depended on colonial government policies arranging access to local land and labour resources. Further, we argue that these policies were shaped by the clashing interests of African smallholders and European planters, in which colonial governments did not necessarily abide to settler demands, as is often assumed.
Keywords: 330; cash-crop production; colonial history; settler farming; Sub-Saharan Africa